A Painting Show : Deweer Art Gallery 1979-1994. - Coucke, Jo (Otegem : Deweer Art Gallery, 1994)
Anzinger, Siegfried ; Baselitz, Georg ; Brumberg, Keith ; Carroll, Lawrence ; DC, Franky ; Dessi, Gianni ; Dokoupil, Jiri Georg ; Fetting, Rainer ; Förg, Günther ; Höckelmann, Antonius ; Kirkeby, Per ; Knoebel, Imi ; Lange, Thomas ; Leroy, Eugène ; Müller, Josef Felix ; Paladino, Mimmo ; Penck, A.R. ; Raveel, Roger ; Richter, Gerhard ; Tchouikov, Ivan ; Toebosch, Moniek ; Tuymans, Luc ; Uslé, Juan ; Vandekerckhove, Hans ; Wallinger, Mark
A Painting Show : Deweer Art Gallery 1979-1994, Deweer Art Gallery, Otegem (Zwevegem), 15.10 - 18.12.1994
Nederlands & Engels
kunstcatalogus